2018
DOI: 10.1101/452912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidation-induced destabilization of the fibrinogenαC-domain dimer investigated by molecular dynamics simulations

Abstract: Pederson et al., Oxidation of fibrinogen αC domain 2 Abstract Upon activation, fibrinogen is converted to insoluble fibrin, which assembles into long strings called protofibrils. These aggregate laterally to form a fibrin matrix that stabilizes a blood clot. Lateral aggregation of protofibrils is mediated by the αC domain, a partially structured fragment located in a disordered region of fibrinogen. Polymerization of αC domains links multiple fibrin molecules with each other enabling the formation of thick fib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Our results showed that the effect on clot turbidity was nearly identical to that seen with oxidation. This observation supports MD simulations pointing towards a potential mechanism by which oxidation of the AαC domain inhibits lateral proto bril aggregation due to partial burying of local polymerization binding sites 26 making lateral aggregation of brin monomers energetically unfavorable 33,34 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results showed that the effect on clot turbidity was nearly identical to that seen with oxidation. This observation supports MD simulations pointing towards a potential mechanism by which oxidation of the AαC domain inhibits lateral proto bril aggregation due to partial burying of local polymerization binding sites 26 making lateral aggregation of brin monomers energetically unfavorable 33,34 .…”
Section: Discussionsupporting
confidence: 82%
“…For instance, an increase of T 2 was detected in articular cartilage degraded by collagen and loss of proteoglycan, resulting in an abnormal structural collage network 38 . Applying this approach to study brin clot structure after oxidation, we found that HOCl oxidation made brinogen less accessible to water molecules and prevented water-protein interactions, which may have direct effects of burying the active binding sites in the alpha C domains and inhibiting dimerization between brinogen molecules 33,34 . The total T 1 /T 2 ratio of water protons was increased upon conversion of brinogen solution to plasma brin gel (refer to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus picture was that the αC‐regions following FpB cleavage extend further and help the lateral aggregation of fibrils by binding to each other. Furthermore, a very recent molecular dynamics simulation investigated the role of a particular residue, AαM476, located in the β‐hairpin present within the only (partially) structured domain so far identified in the αC‐region.…”
Section: Discussionmentioning
confidence: 99%
“…Further, six methionine oxidized fibrinogen peptides were more abundant in ZIKV patients. Methionine oxidation in fibrinogen can change protein structure and impair aggregation and coagulation (Weigandt et al 2012; White et al 2016; Pederson and Interlandi 2019). The known modification sites were consistent with one of the modifications we identified in Fibrinogen A (residue 495) which was significantly less abundant in ZIKV patients.…”
Section: Resultsmentioning
confidence: 99%